Предмет: Алгебра,
автор: нурка14
(x-2)(x^2+2x+1)=4(x+1)
Ответы
Автор ответа:
0
Решение
(x-2)(x^2+2x+1)=4(x+1)
x³ + 2x² + x - 2x² - 4x - 2 = 4x - 4
x³ - 7x - 6 = 0
x₁ = - 1
x³ - 7x - 6 Ix + 1I
-(x³ + x²) I x² - x - 6
- x² - 7x
-(-x² - x)
- 6x - 6
-(-6x - 6)
0
x³ - 7x - 6 = (x + 1)*(x² - x - 6)
x² - x - 6 = 0
x₂ = - 2
x₃ = 3
Ответ: x₁ = - 1 ; x₂ = - 2 ; x₃ = 3
(x-2)(x^2+2x+1)=4(x+1)
x³ + 2x² + x - 2x² - 4x - 2 = 4x - 4
x³ - 7x - 6 = 0
x₁ = - 1
x³ - 7x - 6 Ix + 1I
-(x³ + x²) I x² - x - 6
- x² - 7x
-(-x² - x)
- 6x - 6
-(-6x - 6)
0
x³ - 7x - 6 = (x + 1)*(x² - x - 6)
x² - x - 6 = 0
x₂ = - 2
x₃ = 3
Ответ: x₁ = - 1 ; x₂ = - 2 ; x₃ = 3
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Беларуская мова,
автор: nastuak8
Предмет: Алгебра,
автор: BatmanDoge
Предмет: Информатика,
автор: Xami5433
Предмет: Математика,
автор: Vitalik12795